PtZn‐ETS‐2: A novel catalyst for ethane dehydrogenation. Issue 12 (25th August 2015) - Yu, Zhengnan; Sawada, James A.; An, Weizhu; Kuznicki, Steven M.
Abstract : Catalysts having unprecedented selectivity toward ethane dehydrogentation were prepared by combining platinum and zinc on the surface of the titanate ETS‐2. This high surface area, sodium titanate ion exchanger affords high metal dispersion, presents many active sites to the gas stream, and is free of any pore structure that can influence mass transfer to and away from the active sites. It was determined that the addition of zinc to platinum‐loaded ETS‐2 changes the electronic properties of the metals and significantly improves the specificity of the catalyst. By changing the zinc‐to‐platinum ratio, and by manipulating the space velocity of the gas, the production of side products and coke can be suppressed or eliminated. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4367–4376, 2015